2002
DOI: 10.1046/j.1460-9592.2002.00801.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fast versus slow rewarming following acute moderate hypothermia in rats

Abstract: In rats, moderate hypothermia for 20 min does not appear to cause lasting biochemical or behavioural consequences, whether rewarming lasted over 30 or 120 min. However, there was a greater early change in cardiac output and heart rate, due to systemic vasodilatation in the fast rewarming animals. These acute changes may have consequences in patients with compromised cardiovascular reserves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Clinical studies investigating the therapeutic use of hypothermia recommend a warming rate no faster than 0.5°C/h [28].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies investigating the therapeutic use of hypothermia recommend a warming rate no faster than 0.5°C/h [28].…”
Section: Discussionmentioning
confidence: 99%
“…Although optimal methods for re-warming were not tested in newborn animals, adult animal studies indicated that slow re-warming was preferred. 15,16 …”
Section: Pathophysiologic Basis For Therapeutic Strategiesmentioning
confidence: 99%
“…Evaluations of animal models including fetal sheep, newborn mice, rat pups, piglets, and nonhuman primates27, 9, 12, 13, 15, 16, 2324 with timed hypoxic-ischemic injury have been performed and been reviewed 25, 26…”
Section: Pathogenesis Of Hiementioning
confidence: 99%